2020
DOI: 10.3390/s20102980
|View full text |Cite
|
Sign up to set email alerts
|

Directional Response of Randomly Dispersed Carbon Nanotube Strain Sensors

Abstract: Tests on a double lap bonded joint, with transverse strips of randomly oriented carbon nanotubes (CNT) sprayed onto an epoxy adhesive film, showed a positive increment in electrical resistance under tensile load, even though the transverse strains were negative. Other experiments included in this work involved placing longitudinal and transversal CNT sensors in a tensile loaded aluminum plate, and, as reported by other authors, the results confirm that the resistance change is not only dependent on the strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…For instance, in case of 4fCNT‐S composite film, the ΔRnormalsRnormali showed a strain‐independent behavior up till ε = 0.031 (see inset of Figure 4b). The strain‐independent behavior is most likely due to the following reasons: (i) the percentage of CNT content (4 wt%) is much higher than the PT of the composite, leading to a denser CNT network and multiple conducting paths, thus no change in resistance with strain and (ii) alignment of randomly oriented CNTs in composites in the initial stage of applied strain 16,65 . Another reason may be the small resistance change that is beyond the capability of measuring equipment.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in case of 4fCNT‐S composite film, the ΔRnormalsRnormali showed a strain‐independent behavior up till ε = 0.031 (see inset of Figure 4b). The strain‐independent behavior is most likely due to the following reasons: (i) the percentage of CNT content (4 wt%) is much higher than the PT of the composite, leading to a denser CNT network and multiple conducting paths, thus no change in resistance with strain and (ii) alignment of randomly oriented CNTs in composites in the initial stage of applied strain 16,65 . Another reason may be the small resistance change that is beyond the capability of measuring equipment.…”
Section: Resultsmentioning
confidence: 99%
“…To date, SHM with carbon nanoparticles is focused mainly on CNT and graphene nanoplatelet (GNP)-based nanocomposites. As a general trend, it is observed that GNP-based composites exhibit higher sensitivities than CNT-based ones, with gauge factors (GFs), defined by the change on normalized resistance divided by applied strain, that can range from values of 11 to 40 [ 28 , 29 , 30 , 31 ] and 1 to 4 [ 26 , 32 , 33 ] at low strain levels for GNPs and CNTs, respectively. This can be explained because the 2D distribution of GNPs allows higher interparticle distance between adjacent nanoparticles.…”
Section: Introductionmentioning
confidence: 99%